Prognosis of Traumatic Ulnar Nerve Injuries: A Systematic Review. (January 2019) - Lan, Ching-Yu; Tien, Huey-Yuan; Lin, Yu-Te; Hsu, Chun-Cheng; Lin, Cheng-Hung; Chen, Shih-Heng
Abstract : Abstract: Ulnar nerve injury (UNI) is not uncommon and often results in incomplete motor recovery after the initial nerve repair and requires secondary functional reconstruction. To clarify the prognosis and predicting factor of UNI, and if it is reasonable to wait after the initial repair, a systematic literature review from PubMed computerized literature database and Google scholar was performed. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist and guidelines were followed to develop the search protocol for this literature review. Two reviewers independently assessed titles, abstracts, and full-text articles, and a third reviewer resolved any disagreements. Seventeen articles with 260 cases were found with sufficient data and enough follow-up. After multiple logistic regression, age, injury level, gap of lesion, and delayed time to surgery were significant prognostic factors in UNI. If considering only high-level injuries (injury at or above proximal forearm), age became the only predicting factor. In cases with likely poor prognosis, their motor recovery tends to be unsatisfactory, and observation for months after the initial repair might not be reasonable. Other surgical interventions such as early nerve transfer may be an option to improve the outcome.